Palynology of the genus Lagerstroemia (Lythraceae) in Thailand - SURAPON SAENSOUK; PIYAPORN SAENSOUK (Society for Indonesian Biodiversity, 2023)
Abstract. Saensouk S, Saensouk P. 2023. Palynology of the genus Lagerstroemia (Lythraceae) in Thailand. Biodiversitas 24: 3222-3229. Pollen morphology of Lagerstroemia (Lythraceae) from Thailand was poorly reported. This study aimed to study the pollen morphology of 17 species of the genus Lagerstroemia in Thailand by applying acetolysis under a light microscope and scanning electron microscope. Pollen of the genus Lagerstroemia in Thailand was described with the distinctive features of the pollen morphology, i.e., size, shape, exine sculpturing, the character of the aperture, polar, and symmetry. All pollen grains were monad with and polar view length of 43.83±2.84 µm, and equatorial view length of 26.33±2.05 µm. The shape of pollens was prolate spheroidal, subspheroidal, spheroidal, and subprolate. The pollens in this study were recognized as bilateral, radial, and sub-radial symmetries. All pollen grains were apolar and polar. The aperture of all pollen species in this study was reported with tricolpate and tricolporate. Exine sculpturing was exine sculpturing and scabrate-granulate. The pollen morphology of this study can be divided into groups based on shape, exine sculpturing, the character of the aperture, polarity, and symmetry. Pollen sizes of all species were medium size. The pollen ofall species from Thailand are reported as Lagerstroemia indica-type.The pollen morphology in this study cannot be used for species identification. Pollen of 16 Lagerstroemia species were studied here for the first time.